Development and characterisation of novel electrospun polylactic acid/tubular clay nanocomposites - Dong, Yu; Chaudhary, Deeptangshu; Haroosh, Hazim; Thomas, Bickford (Springer, 2011)
A novel material formulation method of polylactic acid /tubular clay nanocomposites via electrospinning was introduced and the important processing parameters such as solution concentration, clay loading, material feed rate were particularly investigated. The hybrid fibre diameter, the clay dispersability and the thermal properties of such nanocomposites were then characterised by using the scanning electron microscopy, wide-angle X-ray diffraction and differential scanning calorimetry, respectively, to establish a fundamental structure–property relationship for the future application.